From the Euripides’ "Hippolytus" to Manuel Lourenzo’ "Romería ás covas do demo": some passages of confluence - Cendán Teijeiro, Noelia (Madrygal. Revista de Estudios Gallegos, 2012)
The intellectual and textual relation between the Galician farce Romería ás covas do demo of Manuel Lourenzo with the Greek tragedy Hippolytus of Euripides is the center of interesting processes of literary manipulation and recreation. Indeed, the aim of this article is the approach to the study of the foregoing.
Keywords: Romería ás covas do demo; Manuel Lourenzo; Hippolytus; Euripides; literary recreation.